IoT Technology and its Applications in Various Fields - Devi, Aruna T; Narendra, Suman; Poojitha, Musani (International Journal of Computer Sciences and Engineering, 2025)
Now a day’s smart technology is replacing each and everything in the world. Internet of Things (IoT) has emerged powerfully as a more successful area to express new technologies. Current society is seeing a different flow in the number and domain of devices deployed and used in regular applications, including mobile phones, tablets, wearable devices, and other connected sensing devices, collectively referred to as the IoT. Internet of Things has grown into the lives of human being by allowing a communications between machines, objects and things along with people. The people, software systems and other machines are surrounded with IoT permitted objects which communicate about the present view of things. The world is becoming smarter in all aspect by using IoT technology. IoT features are provided in many of the applications like smart healthcare, smart homes, smart cities, smart energy, waste management, transportation and monitoring type. In IoT technology the physical objects are embedded with RFID, sensors and Internet protocols which allow object to communicate with each other. This paper highlights the application of IoT used in various fields and a review on the concept of IoT related technologies with the advantages and disadvantages that are encountered.